Increased expression of the MALE STERILITY1 transcription factor gene results in temperature-sensitive male sterility in barley - Fernández-Gómez, José (J Exp Bot, 2020)
Understanding the control of fertility is critical for crop yield and breeding; this is particularly important for hybrid breeding to capitalize upon the resultant hybrid vigour. Different hybrid breeding systems have been adopted; however, these are challenging and crop specific. Mutants with environmentally reversible fertility offer valuable opportunities for hybrid breeding. The barley HvMS1 gene encodes a PHD-finger transcription factor that is expressed in the anther tapetum, which is essential for pollen development and causes complete male sterility when overexpressed in barley. This male sterility is due at least in part to indehiscent anthers resulting from incomplete tapetum degeneration, failure of anther opening, and sticky pollen under normal growth conditions (15 °C). However, dehiscence and fertility are restored when plants are grown at temperatures >20 °C, or when transferred to >20 °C during flowering prior to pollen mitosis I, with transfer at later stages unable to rescue fertility in vivo. As far as we are aware, this is the first report of thermosensitive male sterility in barley. This offers opportunities to understand the impact of temperature on pollen development and potential applications for environmentally switchable hybrid breeding systems; it also provides a ‘female’ male-sterile breeding tool that does not need emasculation to facilitate backcrossing.